Remote workforce training : effective technologies and strategies - Hai-Jew, Shalin; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2014)
"This book investigates methods, techniques, and systems used in employee training programs, examining tools and technologies to help employers take their workers beyond the transient skill sets offered by university degrees and into a constant state of learning and practice that will enhance both their productivity and technical abilities on a regular basis"--Provided by publisher.
Four strategies for remote workforce training, development, and certification / Robert Gibson -- Strategic management of workplace e-learning / Jason G. Caudill, Barry Reeves -- Constructing a unified framework and a causal model of occupational satisfaction, trainee reactions, perception of learning, and perceived training transfer / Kijpokin Kasemsap -- Online policy-compliance training in higher education: a preliminary design model / Shalin Hai-Jew -- Teacher professional development: remote podcasting and metacognitive strategies / Tsung-Jui Tsai, Ya-Chun Shih -- The power of e-learning: an effective solution for Turkish police management training courses / Ali Semerci, Hafize Keser, M. Yasar Ozden -- Effective technologies and strategies for the development of teachers and school leaders: case studies from the Northern Territory of Australia / Kathryn Moyle, Glen Speering, Donna Murray, Jon Mason -- Lessons learned from distance workforce training applications: example from cooperative extension / Benjamin Chapman, Sarah D. Kirby, Katrina Levine -- Analyzing work teams using social network diagrams / Shalin Hai-Jew -- Using stranger small world networks for e-marketing in academia / Shalin Hai-Jew -- In Plaintext: electronic profiling in public online spaces / Shalin Hai-Jew -- Learning4Content: WikiEducator's training initiative in education / Ramesh C. Sharma -- Iff and other conditionals: expert perceptions of the feasibility of massive open online courses (MOOCs)--a modified E-Delphi study / Shalin Hai-Jew.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 03/22/2014).
Keywords: Employees -- Training of; Employees -- Training of -- Computer-assisted instruction; Virtual work teams; Telematics; Collaborative training; E-learning; Electronic profiling; Massive open online courses; Occupational satisfaction; Professional development; Social networking applications; Strategic management; Team building; Training applications; Electronic books